2015
DOI: 10.1063/1.4935846
|View full text |Cite
|
Sign up to set email alerts
|

On the estimation of sound speed in two-dimensional Yukawa fluids

Abstract: International audienceThe longitudinal sound speed in two-dimensional Yukawa fluids is estimated using the conventional hydrodynamic expression supplemented by appropriate thermodynamic functions proposed recently by Khrapak et al. [Phys. Plasmas 22, 083706 (2015)]. In contrast to the existing approaches, such as quasi-localized charge approximation (QLCA) and molecular dynamics simulations, our model provides a relatively simple estimate for the sound speed over a wide range of parameters of interest. At stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 47 publications
4
26
0
Order By: Relevance
“…Its accuracy serves as an important check of the reliability of the proposed approximation. Comparison between the calculation using formula (16) and accurate MD results for the pressure of 2D Yukawa fluids tabulated by Kryuchkov et al 21 is shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 91%
“…Its accuracy serves as an important check of the reliability of the proposed approximation. Comparison between the calculation using formula (16) and accurate MD results for the pressure of 2D Yukawa fluids tabulated by Kryuchkov et al 21 is shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 91%
“…This functional form has been proven to be very useful for various fluids characterized by soft long-ranged interactions in 2D. 31,32,88,89 Appendix B: Simplified expressions for L and T The explicit expressions for L(k) and T (k) for the 2D Coulomb system are 21,55 L 2 (k) = ω 2 0 q + ω 2 0 ∞ 0 h(x) 2x 2 [1 − J 0 (qx) + 3J 2 (qx)] dx,…”
Section: Discussionmentioning
confidence: 99%
“…For strongly coupled Yukawa systems we have γ 1, which is a general property of soft repulsive interactions. [54][55][56] This fluid approach has been exploited previously for Yukawa systems in 3D case 10,54 as well as in 2D case. 55 Generalization to 1D case is trivial.…”
Section: Sound Velocities In Different Spatial Dimensionsmentioning
confidence: 99%